A comparative study of patients' preferences and sensory perceptions of three forms of inhalers among Thai asthma and COPD patients - Bunnag C. (2014)
In 9 study centers, 419 patients with asthma or COPD were randomized to receive two forms of salbutamol metered-dose-inhalers (MDIs), i.e. CFC-driven MDI, non-CFC (HFA) MDI and one salbutamol dry powder inhaler (DPI), in a multi-center, comparative, cross-over and randomized study, performed to facilitate the formulation of a strategic plan to phase out CFC MDIs. After having received all three forms of test products, the patients completed an evaluation questionnaire indicating their preferences, likelihood of treatment compliance on each product and the easiest one to use. Statistical analysis showed that the CFC MDI was significantly less irritating (p < 0.014) but lower in its overall appeal (p < 0.0001). The "most preferred form to be prescribed" was DPI at 47.5% followed by non-CFC at 32.5% and CFG MDI at 20.1 %. Concerning the ease of use among the three forms of test products, 59.9% of the patients indicated "no difference". Adverse events were mild and occurred in only 8.2%. In conclusion, patients' preference and sensory perception among the three forms of inhalers were comparable except that the CFC MDI was significantly less irritating but lower in its overall appeal. DPI was the most preferred and easiest form to use but also the most expensive. Taking public health into consideration, a non-CFC MDI with a similar market price to the CFC MDI would be the obvious choice in a strategic plan to phase out CFC MDIs with the least difficulty to the consumers.